Implementation of Transparency Principles in Governance of Sidenreng Rappang Regency - Indirwan, Sry Iin; Sam, Muliani; Nilwana, Andi; Irwan, Irwan (Universitas Pancasakti, 2025)
This study explores the implementation of transparency principles in local governance in Sidenreng Rappang Regency using a qualitative descriptive approach. Using the Humanitarian Forum Indonesia (HFI) framework, this study focuses on six main principles of transparency, including access to public information, financial reporting, media publication, and institutional guidelines. Data were collected through in-depth interviews with government officials from Bappeda, Kominfo, and the Finance Office, in addition to document analysis and thematic coding using NVivo. The results show that transparency is systematically promoted through digital platforms, financial dissemination, and public engagement. However, several challenges remain, such as inconsistent implementation of SOPs across institutions, uneven bureaucratic capacity, and limited public understanding of published data. The study concludes that while transparency has become an integral part of governance practices in Sidrap, its full institutionalization requires stronger inter-agency coordination, improved public communication strategies, and standardized information management protocols. These findings contribute to a deeper understanding of how local transparency practices align with good governance and institutional strengthening goals.